MAPPING SELF SUPPORT THROUGH THE UTILIZATION OF INFORMATION TECHNOLOGY IN COMMUNITY-BASED SETTLEMENTS - Osin Djuma,; Novita Tune,; Abdul Rahmat,; Ummyssalam ATAD Duludu,; Pravin R. Choube, (International Journal of Innovations in Engineering Research and Technology, 2023)
Mapping self-subsistent is method collection information about potentials and problems of the residential environment in a participatory way through the process of focus group discussions, tracing field conditions, and digital data mapping. Objective from activity This is give information base about opportunities and problems environment settlement through participation society. Another goal of study This For understand the empowerment process through non-formal education in carry out activity utilization technology information on settlements based society. Mapping done through three stage that is preparation, data review and formulation . Based on results implementation activity society, compiled a number of map thematic opportunities and problems in field economics, cultivation , network roads , management trash , drainage and sanitation . Mapping through mapping self has two roles main , as a participatory process and as product the community created . Mapping through mapping independent has two roles main , as a participatory process and as the resulting product society .